Learning the city : knowledge and translocal assemblage - McFarlane, Colin (Malden, MA : Wiley-Blackwell, 2011)
"Learning the City critically examines the relationship between knowledge, learning, and urbanism. It argues both for the centrality of learning for political strategies and for a resurgence of learning that represents a critical opportunity to develop a progressive international urbanism. The author combines the result of his fieldwork conducted in Mumbai and other regions with a synthesis of the most current theoretical research on knowledge, space, and materiality to show how learning should be viewed as central to the production and politics of cities. In doing so, he deploys the analytic of assemblage to explain the complex processes through which knowledge and learning enable and limit various forms of urbanism. This groundbreaking work examines learning as a practice, explores learning as tactics, and reveals how learning is intrinsic to the shape of political imaginaries, strategies, and contestations. A critical discussion of the types of learning environments that may facilitate more socially just urbanisms is also included. Provocative, timely, and fraught with scholarly rigor, Learning the City offers invaluable insights into the role of learning in urban developmental studies"--Provided by publisher.
Learning assemblages -- Assembling the everyday: incremental urbanism and tactical learning -- Learning social movements: tactics, urbanism and politics -- Urban learning forums -- Travelling policies, ideological assemblages -- A critical geography of urban learning -- Conclusion.
Includes bibliographical references (p. [185]-204) and index.
Keywords: Sociology